Factors Affecting Pregnant Women's Behavior in Conducting HIV Examination in Belawan Health Center of Medan Belawan District in 2018 - Maulinda, Vira; Kahar, Irawaty. A; Purba, Agnes (Sari Mutiara Indonesia University Press, 2018)
HIV is a virus which can decrease one’s immunity. In pregnancy, it can have a high risk for infection from a mother to her baby so that when it is not handled immediately, it will cause a big health problem throughout the world. The research was conducted at Belawan Puskesmas, Medan Belawan Subdistrict. The objective of the research was to find out whether there was significant influence of knowledge, attitude, perception, self-vulnerability, husbands’ support, and health care providers’ support on pregnant women’s behavior in having HIV examined. The research used quantitative analytic correlation method with cross sectional design. The population was all pregnant women who visited the Puskesmas to do antenatal care, and 83 of them were used as the samples, taken by using Sloivin formula. The result of the research showed that there was significant influence of knowledge, attitude, perception, self-vulnerability, husbands’ support, and health care providers’ support on pregnant women’s behavior in having HIV examined. The result of multiple logistic regression analysis showed that the variable which had the most dominant influence was husbands’ support which had the opportunity of 11.136 times of having HIV examined compared with husbands who did not support. It is recommended that pregnant women always participate in counseling in order to add their knowledge and insight in all indicators when they have HIV examined and to prevent from their negative attitude toward HIV examination.